2019
DOI: 10.1186/s12864-019-5668-3
|View full text |Cite
|
Sign up to set email alerts
|

Aging in the Drosophila ovary: contrasting changes in the expression of the piRNA machinery and mitochondria but no global release of transposable elements

Abstract: Background Evolutionary theory indicates that the dynamics of aging in the soma and reproductive tissues may be distinct. This difference arises from the fact that only the germline lineage establishes future generations. In the soma, changes in the landscape of heterochromatin have been proposed to have an important role in aging. This is because redistribution of heterochromatin during aging has been linked to the derepression of transposable elements and an overall loss of somatic gene regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 89 publications
1
10
3
Order By: Relevance
“…Selected populations subsequently increased whereas controls decreased expression, meeting at a similar expression level at old age. This is comparable with recent studies which suggested that age-dependent changes in TE expression differ between genotypes ( Erwin and Blumenstiel 2019 ; Everett et al 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Selected populations subsequently increased whereas controls decreased expression, meeting at a similar expression level at old age. This is comparable with recent studies which suggested that age-dependent changes in TE expression differ between genotypes ( Erwin and Blumenstiel 2019 ; Everett et al 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…Opposing our hypothesis, two recent studies in termites ( Elsner et al 2018 ) and D. melanogaster ( Erwin and Blumenstiel 2019 ) suggest that the germline is protected from TE invasions through increased transcription of the piRNA machinery. Indeed, our expression analysis confirms that many genes associated with transcriptional and post-transcriptional TE silencing tend to be upregulated with age.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In line with termite workers, increased TE activity with age occurs in Drosophila somatic tissues [19][20][21], albeit with the caveat that TE insertion rates are prone to overestimation in sequencing data [22]. It has been hypothesised that that age-related misexpression of TEs is restricted to somatic tissues due to continued efficient policing of the germline by the piRNA response with age [17,18,23].…”
Section: Ageing and The Pirna Pathway In Arthropodsmentioning
confidence: 87%